Ptychographic X-ray tomography reveals additive zoning in nanocomposite single crystals - Ihli, Johannes (Royal Society of Chemistry, 2019)

(untitled) (Chem Sci)
Single crystals containing nanoparticles represent a unique class of nanocomposites whose properties are defined by both their compositions and the structural organization of the dispersed phase in the crystalline host. Yet, there is still a poor understanding of the relationship between the synthesis conditions and the structures of these materials. Here ptychographic X-ray computed tomography is used to visualize the three-dimensional structures of two nanocomposite crystals – single crystals of calcite occluding diblock copolymer worms and vesicles. This provides unique information about the distribution of the copolymer nano-objects within entire, micron-sized crystals with nanometer spatial resolution and reveals how occlusion is governed by factors including the supersaturation and calcium concentration. Both nanocomposite crystals are seen to exhibit zoning effects that are governed by the solution composition and interactions of the additives with specific steps on the crystal surface. Additionally, the size and shape of the occluded vesicles varies according to their location within the crystal, and therefore the solution composition at the time of occlusion. This work contributes to our understanding of the factors that govern nanoparticle occlusion within crystalline materials, where this will ultimately inform the design of next generation nanocomposite materials with specific structure/property relationships.